Comprehensive analysis of alternative splicing in Rosa roxburghii Tratt reveals its role in flavonoid synthesis - An, Yanlin; Wu, Jiahua; Chen, Yani; Li, Shize (Frontiers in Plant Science, 2025)
IntroductionAlternative splicing (AS) plays an important role in the synthesis of plant metabolites. Chestnut rose is a fruit with rich metabolites and health benefits. However, the role of AS in its metabolite synthesis is rarely reported.MethodsThe transcriptome data of eight tissues of Rosa roxburghii were analyzed by using Trimmomatic, Hisat2 and StringTie software. AStalavista tool was used to identify alternative splicing (AS) events, which were further analyzed with IGV browser and other tools. The WGCNA package in R software was applied to construct co-expression networks. AS events were validated by RT-qPCR, and the RrActin was used as an internal control to analyze the transcription expression pattern.ResultsIn this study, the AS landscape were characterized in different tissues of chestnut rose. The data showed that 8586 genes could undergo AS and a total of 49,523 AS events were generated. Among them, tissue-specific AS genes were found in leaves, flowers and fruits. The content of flavonoids in the samples was detected and WGCNA analysis was performed with the AS genes. Five key modules of AS genes related to flavonoid synthesis were identified, and 4CL, ANR, DFR, MYB and other AS genes were validated by PCR and sequencing. In addition, qRT-PCR analysis revealed that the expression level of basic helix-loop-helix (bHLH) transcription factor AS transcript was higher than its full-length transcript, and it was highly expressed in FR1 and significantly correlated with flavonoids.DiscussionOur research identified AS events in different tissues of chestnut rose and revealed their important functions in flavonoid synthesis. This study provides the basis for the molecular mechanism of flavonoids in chestnut rose.